Effect of aging on hypopharyngeal safe volume and the aerodigestive reflexes protecting the airways. (29th April 2014) - Dua, Kulwinder S.; Surapaneni, Sri Naveen; Kuribayashi, Shiko; Hafeezullah, Mohammed; Shaker, Reza
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Studies on young volunteers have shown that aerodigestive reflexes are triggered before the maximum volume of fluid that can safely collect in the hypopharynx before spilling into the larynx is exceeded (hypopharyngeal safe volume [HPSV]). The objective of this study was to determine the influence of aging on HPSV and pharyngo‐glottal closure reflex (PGCR), pharyngo‐UES contractile reflex (PUCR), and reflexive pharyngeal swallow (RPS). Study Design Comparison between two groups of different age ranges. Methods Ten young (25 ± 3 standard deviation [SD] years) and 10 elderly (77 ± 3 SD years) subjects were studied. PGCR, PUCR, and RPS were elicited by perfusing water into the pharynx rapidly and slowly. HPSV was determined by abolishing RPS with pharyngeal anesthesia. Results Frequency–elicitation of PGCR and PUCR were significantly lower in the elderly compared to the young during slow water perfusion (47% vs. 97% and 40% vs. 90%, respectively, P < .001). RPS was absent in five of the 30 (17%) slow injections in the elderly group. In these elderly subjects, HPSV was exceeded and laryngeal penetration of the water was seen. The threshold volume to elicit PGCR, PUCR, and RPS was significantly lower than the HPSV during rapid injections. Except for RPS, these volumes were also significantly lower than HPSV during slow injections. Conclusions PGCR, PUCR, and RPS reflexes are triggered at a threshold volume significantly lower than the HPSV in both young and elderly subjects. Lower frequency–elicitation of PGCR, PUCR, and RPS in the elderly can predispose them to the risks of aspiration. Level of Evidence 4. Laryngoscope, 124:1862–1868, 2014